2018
DOI: 10.14814/phy2.13660
|View full text |Cite
|
Sign up to set email alerts
|

Past injurious exercise attenuates activation of primary calcium-dependent injury pathways in skeletal muscle during subsequent exercise

Abstract: Past contraction‐induced skeletal muscle injury reduces the degree of subsequent injury; this phenomenon is called the “repeated bout effect (RBE).” This study addresses the mechanisms underlying the RBE, focusing on primary calcium‐dependent injury pathways. Wistar rats were subdivided into single injury (SI) and repeated injury (RI) groups. At age 10 weeks, the right gastrocnemius muscle in each rat in the RI group was subjected to strenuous eccentric contractions (ECs). Subsequently, mild ECs were imposed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…15 Factors contributing to this muscular phenomenon include decreased calcium levels, insufficient oxygen, accumulation of metabolites like lactic acid, and the dephosphorylation of the light chain of myosin, with the latter believed to influence troponin sensitivity to calcium. 16 It is of significant relevance to sports medicine the concept of power, serving as a quantifiable descriptor of muscular activity. Power is determined by the force of contraction and the resultant work, providing valuable insights into muscular performance in clinical sports settings.…”
Section: Discussionmentioning
confidence: 99%
“…15 Factors contributing to this muscular phenomenon include decreased calcium levels, insufficient oxygen, accumulation of metabolites like lactic acid, and the dephosphorylation of the light chain of myosin, with the latter believed to influence troponin sensitivity to calcium. 16 It is of significant relevance to sports medicine the concept of power, serving as a quantifiable descriptor of muscular activity. Power is determined by the force of contraction and the resultant work, providing valuable insights into muscular performance in clinical sports settings.…”
Section: Discussionmentioning
confidence: 99%
“…During exercise, the nervous system releases some neurotransmitters, such as norepinephrine and acetylcholine, which are related to regulating calcium channels and may affect the expression of Cacna2d1 [ 39 ]. In addition, exercise regulates some calcium signaling and affects cellular function and metabolism, decreasing Cacna2d1 expression [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calpains are intracellular calcium-dependent cysteine endopeptidases that get activated by cytosolic Ca 2+ overload. Numerous studies have demonstrated that activation of calcium activator calpain, after I/R injury, leads to degradation of αII-spectrin (32,33) and TRPC6 (34,35), which in turn increases extracellular calcium influx.…”
Section: Discussionmentioning
confidence: 99%